Growth and yield of pearl millet (Pennisetum glaucum L.) using jatropha cuttings and mineral fertilizer on inceptisols of Sudan Savanna, Nigeria - Aliyu, Abdullahi Nuraddeen (2022)
Field trials were conducted in 2018 and 2019 rainy seasons to evaluate the growth, yield and nutrients (NPK) uptake of pearl millet (Pennisetum glaucum L.) as well as soil nutrients status in response to levels of jatropha cuttings (biomass foliage), mineral fertilizer and methods of application of jatropha cuttings, at two locations (Kadawa and Dutsinma) in the Sudan Savanna of Nigeria where affordability and accessability of fertilizer is difficult, hence low income farmers cultivate crops on low fertility soils (Inceptisols). To improve their fertility, these soils require input of large amounts of organic materials such as jatropha cuttings, which is a cheap and accessible resource. The treatments consisted of three levels of jatropha cuttings (0, 5 and 10 t ha-1), three levels of mineral fertilizer (0, half and full recommended rate of 60 kg N ha-1, 30 kg P2O5 ha-1, 30 kg K2O ha-1) and two methods of application (incorporation and surface placement). Treatments were arranged in a Randomized Complete Block Design replicated three times. Jatropha cuttings and mineral fertilizer significantly (p<0.05) improved the growth and yield of pearl millet over control treatment. However, mineral fertilizer was mostly superior to jatropha cuttings in improving the yield and nutrient uptake of pearl millet. From 2018 to 2019, most growth and yield attributes of pearl millet were observed to increase. Significant increases mostly occurred in 2019 season probably due to carryover effect of nutrients. In 2019, incorporation of 10 t ha-1 jatropha cuttings led to significant increase in plant height (167.3-264.3 cm), leaf area (152.3- 282.2 cm2), grain yield (402.6-2192.9 kg ha-1) and stover yield (3557.1-8939.3 kg ha-1). Mineral fertilizer significantly improved plant height (167.3-223.7 cm), grain yield (402.6-3606.9 kg ha-1), stover yield (4698.2-10570 kg ha-1), and NPK uptake. Incorporation of jatropha cuttings was superior to surface placement in enhancing plant height (157.7-264.3 cm), leaf area (164-282.3 cm2), grain yield (438.9-2192.9 kg ha-1) and stover yield (3321.8-7461 kg ha-1). Mostly, pearl millet’s yields recorded positive and significant relationship with plant height, leaf area and nutrients uptake. Soil pH was significantly decreased by mineral fertilizer. Generally, surface application of jatropha cuttings significantly increased organic carbon, total nitrogen, pH and CEC. Mineral fertilizer significantly enhanced available phosphorus. Soil quality was improved by combinations of surface applied jatropha cuttings plus mineral fertilizer. Soil fertility index (SFI) and soil evaluation factor (SEF) correlated positively and significantly with each other and with grain yield or available phosphorus. Significant interactions revealed that incorporation of 10 t ha-1 jatropha cuttings increased plant height (44-58%), leaf area (85.5%), grain yield (286.3%) and stover yield (109.8%). Combination of 10 t ha-1 jatropha cuttings plus half rate of mineral fertilizer was mostly at par with the full rate of mineral fertilizer. Combinations of mineral fertilizer and jatropha cuttings recorded benefit/cost ratios of >1.0. Therefore, surface application of higher rates (≥10 t ha-1) of jatropha cuttings in combination with modest amounts (half recommended rate) of mineral fertilizer can sustainably improve soil fertility and pearl millet productivity in Inceptisols area of Sudan Savanna (Nigeria).